Development of dynamic fault tree model for reactor protection system. Issue 2 (12th October 2020) - Fahmy, Rania A.
Abstract: Due to the importance of the reactor protection system (RPS) safety function in nuclear power plants (NPPs), its reliability analysis is one of the essential parts of the probabilistic safety assessment (PSA) of any NPP. The dynamic fault tree (DFT) technique extends the conventional static fault tree (SFT) by considering the time requirements to model and evaluate the NPP safety. This study develops the DFT model for RPS to achieve a more realistic and accurate representation of the RPS safety analysis taking into consideration the change in k‐out‐of‐n logic during operation due to test and maintenance (T&M) of any channel. Also, it shows the efficiency of the DFT model over the SFT model with respect to the accuracy, complexity, and calculation time which makes it a useful tool to assess the unavailability of RPS and design a proper maintenance program.